Representation of Madurese Local Wisdom in Mudhar Tamim’s Tafsir Qur’anul-Karim Nurul-Huda - Finaldy, Auli Robby; Pranata, Imam Sufardi (TAFSE: Journal of Qur'anic Studies, 2025)
This article examines how Madurese local wisdom is represented in Mudhar Tamim’s Tafsir Qur’anul-Karim Nurul-Huda. Scholarship on Madurese tafsir has largely centered on interpretive method, the history of writing, and networks of exegetes, while the representational work of local cultural references has received less attention. Using qualitative library research, this study analyzes the tafsir as the primary source and draws on relevant secondary literature. Stuart Hall’s theory of representation is operationalized through reflective, intentional, and constructionist readings to examine how meaning is produced through language, symbols, and social context. The analysis shows that local wisdom in Nurul Huda appears in tangible and intangible forms. Tangible references draw on material culture and built space, such as totop bhireng (a sheath for a Madurese sickle-like weapon) and tabing (a woven bamboo wall panel). Intangible references include proverbs, value terms such as andap asor (humility and respectful conduct), and socially salient practices and authority relations, including carok (a ritualized honor duel), critiques of taqlid (uncritical imitation), and the figure of lora (often understood locally as the son of a kyai (a religious leader)). Across the tafsir, these local elements function as interpretive resources that make Qur’anic guidance socially legible and ethically persuasive for Madurese readers. The study contributes to discussions of Tafsir Nusantara by showing how representational analysis clarifies the role of local cultural codes in vernacular Qur’anic interpretation.